Baobab isotope records and rainfall forcing in Southwest Madagascar over the last 700 years - Estelle Razanatsoa; Lindsey Gillson; Grant Hall; Malika Virah-Sawmy; Stephan Woodborne (PLoS ONE, 2026)
Highly resolved climate records for Madagascar are scarce but are essential for understanding of rainfall drivers over time and assessing the risks and likely trajectories of future climate change. We measured variation in the carbon isotopes of baobabs ( Adansonia spp.) which reflect rainfall in southwest Madagascar. The record indicates a decreasing trend of rainfall over the last 700 years with high variability at a centennial-scale. The duration of wetter periods decreased over time with the wettest periods between 1350–1450 CE, after the onset of the Little Ice Age, while the driest period occurred between 1600–1750 CE, during the Maunder Minimum. The results suggest that decadal to centennial rainfall variability in southwest Madagascar is dominated by tropical forcing rather than subtropical forcing. Wetter periods are regulated by the movement and migration of easterly winds linked to the Intertropical Convergence Zone, while dry periods are influenced by the effect of the Pacific Decadal Oscillation linked to the El Niño Southern Oscillation and the sea surface temperature variation in the Southwestern Indian Ocean. The Southern Annular Mode is significantly correlated with the record, but its effect was only visible at the beginning of the record around 1300 CE. This evidence provides a new understanding of rainfall across southern Africa and the interaction of global forcing with regional factors. Further investigation is required to improve tree chronology from Southern Hemisphere and understand the migration of the westerlies and its potential future effect on the rainfall in Madagascar. Understanding the interplay between tropical and other rainfall forcings will be essential in assessing likely scenarios of resilience, and adaptive capacity of social-ecological systems in Madagascar.